Global Impacts of Pre- and Post-COVID-19 Pandemic: Focus on Socio-Economic Consequences (2020)
On March 11, 2020, the novel Corona virus disease (COVID-19), was described as a pandemic by World Health Organization (WHO). Globally, the COVID-19 has not only affected the public health socially but also has rigorously affected economically. Substantial declines in income, increase in unemployment, and distractions in the transportation, amenities, and industrial sectors are amongst the major concerns of the pandemic disease extenuation. Furthermore, the governments of most of the countries underestimated the menaces of COVID-19 spread and were typically responsive for the calamities in their respective countries. As outbreak of this pandemic is not likely to wane in the nearby future, preventive actions are prerequisite to prevent infection spread, save people lives and also to save the economic affluence. In this review, based on the present knowledge and available literature, we have demonstrated the various aspects of pre-and post-COVID-19 effects over the social and economic phases worldwide. Moreover, the evidence based data have been summarized regarding threats, social influences, scientific upgrades, moral dynamics, stress and adapting in the pre- and post- COVID-19 situations.